ASOSIASI ANTARA LABA DAN ARUS KAS TERHADAP HARGA SAHAM: BUKTI EMPIRIS PADA PERUSAHAAN KEUANGAN DI BURSA EFEK INDONESIA - Abdullah Taman (Universitas Negeri Yogyakarta, 2009)
The objective of this study is to examine association earnings and cashflow towardshare price of financial companies in Indonesian Stock Exchange. Sample selectionwas held by purposive sampling including fivety three companies during 2003 – 2007.Analysis method utilized was multiple regression to test hypothesis with Eviews3program. The result showed that earnings and cashflow had significantly associationwith share price of financial companies (F-value= 56.8756; p 0.001; and adjustedR2= 0.5144). Furthermore, additional test showed that earnings and financing cashflowhad significantly association with share price of financial companies.Key words: earnings, cash flow, share price, financial companies.